THE INTERNAL AUDITING COURSE IN THE ACCOUNTING CURRICULUM. - van Voorhis, Robert H. (The Accounting Review, 1958)
Abstract The article discusses the content of a training program in internal auditing. An internal auditor is an employee of a particular firm. The internal auditor helps assure the accuracy of financial reports. He functions as an element of management control, reviewing and appraising other management controls to make sure they are operating according to plan and in an effective manner. Textbooks, case problems, and other materials with which to teach a course in internal auditing have been prepared over the years by The Institute of Internal Auditors and its members. Current practices are reported in the Institute's quarterly journal, The Internal Auditor, and in the published proceedings of its annual conferences. The available material is more than adequate to provide a challenging course in internal auditing. Moreover, many teachers who recognize the desirability of the accounting student learning something about internal auditing are convinced that the required amount of knowledge can be presented in a lecture or two in the basic auditing course. Such coverage may possibly be sufficient to alert the prospective public accountant to the existence of the internal auditor and the necessity of reviewing his program on an audit assignment. But it is insufficient to present the philosophy and responsibilities of the growing field in internal auditing.